Changes in cerebral oxygen metabolism and significance in patients with severe head injury - Zhu, Xi (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2006)
OBJECTIVE: To investigate the changes in cerebral oxygen metabolism following head injury and their relationship with intracranial pressure (ICP), cerebral perfusion pressure (CPP), and Glasgow coma scale (GCS)